Fenomena Bangunan Mal dan Pengalaman Estetika Bagi Masyarakat Urban di Jakarta - Nediari, Amarena; Purwana, Christophorus (Humaniora, 2013)
Mall building has become part of the urban living’s lifestyle. Going to the mall is an independent necessity without any emotional bond with others. As a public area, mall has been trying to fulfill urban communities’ needs such as to enlarge employment opportunities as well as to provide an entertainment center for visitors. For most of urban communities, mall is considered to be a solution for all members of family. It is one destination for all. Mall elements consist of anchor, secondary anchor, street mall, and landscaping. They are built in a perfect composition in order to emphasize the main purpose of a mall building as a modern place for trading. Interior design in a mall building is not only to apply a finishing treatment but also to give an aesthetic experience to the visitors. The excitement of being surrounded by beautiful material, attractive colors in luxurious building are some of the impact that gives an aesthetic experience in mall buildings. This meant to attract customer to purchase the product. The phenomenon of mall building is that although the function of mall building has met the urban communities’ demand it also has used the green spaces and spoiled the water absorption.  In order to solve the problems that suitable for this situation, designing an integrated mal with green building concept should be the solution. The solution should be supported with government regulation based on the awareness of environmental friendly, combining a mall building with open space with well designed of landscapingwill offer a new place to gather for urban communities.